The relationship between the components of pulmonary artery pressure remains constant under all conditions in both health and disease - Syyed, Raheel; Reeves, John T; Welsh, David; Raeside, David; Johnson, Martin K; Peacock, Andrew J (Chest, 2008)
The relationships among systolic pulmonary artery pressure (SPAP), diastolic pulmonary artery pressure (DPAP), and mean pulmonary artery pressure (MPAP) have been found to be constant in humans breathing air, at rest, while supine. It would be important for those studying the pulmonary circulation if this relationship were maintained under other circumstances, such as change in posture, during exercise, or after pharmacologic manipulation. In particular, it would be useful if the relationship were maintained when treating pulmonary hypertension because this would allow different methods of measurement to be compared, such as SPAP from echocardiography and MPAP from right heart catheterization. Data were reviewed from both healthy subjects and those with pulmonary hypertension (n = 65) who had a micromanometer-tipped, high-fidelity pulmonary artery catheter inserted for between 6 and 36 h in the Scottish Pulmonary Vascular Unit between 1997 and 2003. The 5-min averages, while the patient was supine at rest, were analyzed by linear regression to compare the response of SPAP and DPAP with MPAP. There were linear relationships (measured in millimeters of mercury) of SPAP with MPAP (SPAP = 1.50 MPAP + 0.46), and DPAP with MPAP (DPAP = 0.71 MPAP - 0.66). These were maintained with a high degree of accuracy following changes in posture and activity. SPAP, MPAP, and DPAP were strongly related, and these relationships were maintained under varying conditions. This finding will allow comparison between invasive and noninvasive descriptions of pulmonary hemodynamics found in the literature.